Social network centrality and hormones: The interaction of testosterone and cortisol. (June 2016) - Ponzi, Davide; Zilioli, Samuele; Mehta, Pranjal H.; Maslov, Alexander; Watson, Neil V.
Highlights: Individuals with high basal testosterone and low basal cortisol had higher levels of betweenness and popularity. The same hormonal profile was not predictive of gregariousness. Cortisol was inversely correlated with gregariousness. Abstract: In this study we tested whether testosterone and cortisol interacted in predicting social network centrality within a male rugby team. Using social network analysis (SNA), three measures of centrality were investigated: popularity (i.e., the number of incoming ties a participant receives), gregariousness (i.e., the number of ties leaving from a participant and reaching out to others), and betweenness (i.e., the number of times a person lies between two other individuals). In line with the idea that testosterone and cortisol jointly regulate the emergence of social status, we found that individuals with high basal testosterone and low basal cortisol were more popular and more likely to act as connectors among other individuals (i.e., betweenness). The same hormonal profile was not predictive of gregariousness. However, in line with the small literature on the topic, we found that cortisol was inversely correlated with gregariousness. Despite the cross-sectional and correlational nature of our research design, these findings represent the first empirical evidence that testosterone and cortisol interact to predict complex measures of social hierarchy position derived from social network analyses.